Twinks, Jocks, and Bears, Oh My! Differing subcultural appearance identifications among gay men and their associated eating disorder psychopathology. (September 2022) - Fogarty, Samuel M.; Walker, D. Catherine
Abstract: Gay men have increased risk of body dissatisfaction and disordered eating compared to heterosexual men, and it is unclear what differentiates their risk for thinness- and muscularity-oriented eating psychopathology. Differing subcultural appearance identifications (SAIs) among gay men are one potential factor that may relate to varied eating psychopathology, but this has not been studied. We examined gay men's SAIs: twinks, jocks, and bears; any "other" self-identified SAI; or no SAI, as well as the relationship between men's SAIs and traditional eating psychopathology and unhealthy dieting (both facets of thinness-oriented psychopathology), and muscularity-oriented psychopathology using univariate ANOVAs controlling for participant age. 264 U.S. gay-identified participants self-reported sexual orientation, SAIs, and eating psychopathology. Self-identified twinks did not report higher traditional eating psychopathology or unhealthy dieting than other SAIs or those without a SAI, as hypothesized. Self-identified twinks, jocks, and bears all reported greater muscularity-oriented eating pathology than those without a SAI. Self-identified jocks also reported higher muscularity-oriented disordered eating than those with an "other" self-identified SAI and bears. Thus, having a SAI may increase risk for disordered eating; specifically, identifying as a twink, jock or bear may confer greater risk for muscularity-oriented eating pathology. Highlights: 115/264 gay men reported a subcultural appearance identification (SAI). SAIs were associated with muscularity eating disorder (ED) symptoms. Jocks, twinks, and bears had higher muscularity ED symptoms vs gay men with no SAI. Twinks did not have elevated dieting or traditional ED symptoms.